Pola Asuh Demokratis Dengan Sibling Rivalry Pada Anak Usia Prasekolah - Endang Khoirunnisa; Berliana Kartikasari (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2018)
Background: The birth of a baby is usually attractive to the parents,but not for the eldest child. The eldest childwill feel jealous, especially when he or she saw his little brother or sister were in the arms of their parents like theeldest child’s experience. The eldest child would feel threatened by the presence of the baby that may receive moreattention. Sibling rivalry or jealousy to his little brother could make the eldest child hates or even hostile to his littlebrother. The factor that affecting sibling rivalry is type of parenting that applied by the parents. Purpose: to know therelationship between democratic parenting with sibling rivalry in preschool children in TK Kuncup Harapan Panggungharjo Sewon BantulMethod: this research is a kind of analytic survey with cross sectional method. Population in this research are parents of the children in TK Kuncup Harapan, to decide the sampling using purposive sampling method and there are35 respondents. Instruments of this research using two questionnaires, democratic parenting questionnaires andsibling rivalry among the preschool children. The data analysis using chi square.Result: The analysis result using chi square method is x1 2count > x2table = 6,818> 3,84 and p value 0,024 <0,05and prevalence ratio 3 (CI 1.2815 - 7.3386) so the H0 is rejectedConclusion: There is a relationship between democratic parenting with sibling rivalry in preschool age childrenand the children whose parents apply democratic parenting have risk three times higher to have sibling rivalry thanchildren whose parents apply democratic parenting.Keywords: democratis parenting, sibling rivalry